2021
DOI: 10.1021/acssynbio.0c00470
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Installation of d-Amino Acids in Gene-Encoded Peptides

Abstract: d-Amino acids can have major effects on the structure, proteolytic stability, and bioactivity of peptides. Proteusin radical S-adenosyl methionine epimerases regioselectively install such residues in ribosomal peptides to generate peptides with the largest number of d-residues currently known in biomolecules. To study their utility in synthetic biology, we investigated the substrate tolerance and substrate–product relationships of the cyanobacterial model epimerase OspD using libraries of point mutants as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…While there have been several previous reports suggesting that RS RiPP maturases have varying levels of promiscuity, , the range of substrates that are processed by PapB, which include not just modified donor and acceptor residues and sequence context, but also the ability to accept unnatural amino acids, foreshadows a much larger substrate scope. We should point out that perhaps our ability to observe this expanded range of reactivity is fortuitous and related to access to a highly active protein.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been several previous reports suggesting that RS RiPP maturases have varying levels of promiscuity, , the range of substrates that are processed by PapB, which include not just modified donor and acceptor residues and sequence context, but also the ability to accept unnatural amino acids, foreshadows a much larger substrate scope. We should point out that perhaps our ability to observe this expanded range of reactivity is fortuitous and related to access to a highly active protein.…”
Section: Discussionmentioning
confidence: 99%
“…when fused to its cognate substrate leader sequence. [16] Proteusin epimerases therefore possess remarkable potential as synthetic tools for introducing peptide-stabilizing residues into therapeutic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Proteusin epimerases displayed astonishing substrate promiscuity regarding epimerized amino acid residues and accepted core sequences. [15,16] Orthologs also produced similar epimerization patterns when supplied with the same substrate, highlighting stringent regioselectivity for these enzymes and suggesting that epimerization patterns are dictated, to an extent, by the core peptide sequence. The cyanobacterial epimerase homolog OspD (see below) was even capable of modifying nonnative peptide sequences from medically relevant targets including glucagon, GnRH, human amyloid β-peptide and protegrin-1 pacities in the 21 st century and the development of tools for the identification of these pathways, the RiPP class has seen a significant expansion that has unveiled a remarkable diversity of novel PTMs.…”
Section: Introductionmentioning
confidence: 89%
“…45,47,48 However, d -amino acid patterns installed by a rSAM epimerase vary greatly depending on the core sequence and it is not yet possible to predict the product stereochemistry. 42…”
Section: Ripp Enzymology That Emulates Structural Features Of Nrps Pr...mentioning
confidence: 99%
“…The rSAM peptide epimerase OspD from the proteusin landornamide pathway has been shown to install d -amino acids in highly diverse unnatural core sequences at many different proteinogenic residues and in different patterns (see Section 2.1 d -Amino acids). 42 Core-swap experiments using chimeric precursors as substrates for various OspD-like proteusin epimerases suggested that core elements rather than epimerase identity largely direct the regiospecificity of modifications to control the pattern of installed d -amino acids. 43 However, the core peptide elements that direct the site(s) of epimerisation are not yet defined and are therefore difficult to predict at this time.…”
Section: Synthetic Biology Approaches and Considerations For Emulatin...mentioning
confidence: 99%